Embolism and mechanical resistances play a key role in dehydration tolerance of a perennial grass Dactylis glomerata L. (17th May 2018) - Volaire, Florence; Lens, Frederic; Cochard, Hervé; Xu, Hueng; Chacon-Doria, Larissa; Bristiel, Pauline; Balachowski, Jennifer; Rowe, Nick; Violle, Cyrille; Picon-Cochard, Catherine
Abstract: Background and Aims: More intense droughts under climate change threaten species resilience. Hydraulic strategies determine drought survival in woody plants but have been hardly studied in herbaceous species. We explored the intraspecific variability of hydraulic and morphological traits as indicators of dehydration tolerance in a perennial grass, cocksfoot ( Dactylis glomerata ), which has a large biogeographical distribution in Europe. Methods: Twelve populations of cocksfoot originating from Mediterranean, Temperate and Northern European areas were grown in a controlled environment in pots. Dehydration tolerance, leaf and stem anatomical traits and xylem pressure associated with 88 or 50 % loss of xylem conductance ( P 88, P 50 ) were measured. Key Results: Across the 12 populations of cocksfoot, P 50 ranged from –3.06 to – 6.36 MPa, while P 88 ranged from –5.06 to –11.6 MPa. This large intraspecific variability of embolism thresholds corresponded with the biogeographical distribution and some key traits of the populations. In particular, P 88 was correlated with dehydration tolerance ( r = –0.79). The dehydration-sensitive Temperate populations exhibited the highest P 88 (–6.1 MPa). The most dehydration-tolerant Mediterranean populations had the greatest leaf dry matter content and leaf fracture toughness, and the lowest P 88 (–10.4 MPa). The Northern populations displayed intermediate trait values, potentially attributable to frost resistance. The thickness of metaxylem vessel walls in stems was highly correlated with P 50 ( r = –0.92), but no trade-off with stem lignification was observed. The relevance of the linkage between hydraulic and stomatal traits is discussed for drought survival in perennial grasses. Conclusions: Compared with woody species, the large intraspecific variability in dehydration tolerance and embolism resistance within cocksfoot has consequences for its sensitivity to climate change. To better understand adaptive strategies of herbaceous species to increasing drought and frost requires further exploration of the role of hydraulic and mechanical traits using a larger inter- and intraspecific range of species.